Chronology and documentary handbook of the State of Texas - Vexler, Robert I. (Dobbs Ferry, N.Y. : Oceana Publications, 1979)
Includes a chronology of events in Texas from 1519 to 1977, a biographical directory, and selected pertinent documents.
Cover title: Texas, a chronology & documentary handbook.
Includes index.
Bibliography: p. 147-148.
Keywords: Texas -- History -- Chronology; Texas -- Biography; Texas -- History -- Sources; Texas -- History